Free-standing 2D nanorafts by assembly of 1D nanorods for biomolecule sensing. Issue 25 (14th June 2019) - Cai, Ren; Du, Yaping; Yang, Dan; Jia, Guohua; Zhu, Bowen; Chen, Bo; Lyu, Yifan; Chen, Kangfu; Chen, Dechao; Chen, Wei; Yang, Lu; Zhao, Yuliang; et al.
Abstract : Novel materials from self-assembled nanocrystals hold great promise for applications ranging from inorganic catalysis to bio-imaging. Abstract : Novel materials from self-assembled nanocrystals hold great promise for applications ranging from inorganic catalysis to bio-imaging. However, because of the inherent anisotropic properties, it is challenging to assemble one-dimensional (1D) nanorods into higher-order structures ( e.g. 2D sheets or 3D networks) without any support. Here, we have developed a facile strategy for the direct self-assembly of 1D nanorods into free-standing 2D nanorafts with lateral dimensions up to several micrometers. As a general approach, 2D nanorafts with diverse compositions, e.g. MgF2, WO2, CdS, ZnS, and ZnSe nanorafts, have been fabricated from the assembly of their 1D building blocks. More importantly, these nanorafts show high stability even when dispersed in different solvents, making them suitable for various applications. Because of their high porosity and strong adsorption capability, MgF2 nanorafts were investigated to illustrate the collective advantages generated from the assembly platform. Moreover, flexibility in the composition and structure of the building blocks demonstrated in this work will lead to next generation materials with rich functionalities.